Platelet Function in Surgical Stress - Naesh, O; Friis, J T; Hindberg, I; Winther, K (Thrombosis and Haemostasis, 1985)
Ten patients for elective cholecystectomy were studied pre-, per- and postoperatively. All had neurolept anesthesia. Plasma concentrations of β-TG, TXB2 and 5-HT and intraplatelet 5-HT were measured. Aggregation to ADP was recorded.Serum cortisol concentration was used as index of the stress response, showing peroperative increase and postoperative decrease. Closely related to this we observed a significant increase in P-β-TG and P-TXB2 with postoperative normalization in 6 patients without complications. P-5-HT had a peak peropera-tively and remained elevated postoperatively. A negative correlation between P--5-HT and decreasing intraplatelet 5-HT postoperatively was observed.High postoperative levels of P--5-HT seem to be related to low arterial Po2 and pulmonary dysfunction. In 3 patients with complications a second increase in P-β-TG, P-TXB2 and partly in P--5-HT was found. Platelets were temporarily refractory to ADP immediately following surgery and showed increased aggregabil-ity postoperatively. We conclude that platelets are activated in surgical stress.
Keywords: Platelet activation; Surgical stress; Beta-thromboglobulin; Thromboxane; 5-hydroxytryptamine